Timing Effects of Heat-Stress on Plant Ecophysiological Characteristics and Growth - Wang, Dan; Heckathorn, Scott A.; Mainali, Kumar; Tripathee, Rajan (Frontiers in Plant Science, 2016)
More intense, more frequent, and longer heat-waves are expected in the future due to global warming, which could have dramatic agricultural, economic and ecological impacts. This field study examined how plant responded to heat-stress (HS) treatment at different timing in naturally-occurring vegetation. HS treatment (5 days at 40.5 ºC) were applied to 12 1m2 plots in restored prairie vegetation dominated by Andropogon gerardii (warm-season C4 grass) and Solidago canadensis (warm-season C3 forb) at different growing stages. During and after HS, air, canopy, and soil temperature were monitored; net CO2 assimilation (Pn), quantum yield of photosystem II (ФPSII), stomatal conductance (gs), and internal CO2 level (Ci) of the dominant species were measured. One week after the last HS treatment, all plots were harvested and the biomass of above-ground tissue and flower weight of the two dominant species was determined. HS decreased physiological performance and growth for both species, with S. canadensis being affected more than A. gerardii, indicated by negative heat stress effect on both physiological and growth responses. There were significant timing effect of heat stress on the two species, with greater reductions in the photosynthesis and productivity occurred when heat stress was applied at later-growing season. The reduction in aboveground productivity in S. canadensis but not A. gerardii could have important implications for plant community structure by increasing the competitive advantage of A. gerardii in this grassland. The present experiment showed that heat stress, though ephemeral, may promote long-term effects on plant community structure, vegetation dynamics, biodiversity, and ecosystem functioning of terrestrial biomes when more frequent and severe heat stress occur in the future.